A Study on Perceived value of Food and Nutritional Choices and Their Relative Impact on Academic Performance and Competence Among College Professors in select districts of Karnataka (International Journal of Food and Nutritional Sciences, 2022)
This study explores the relationship between food and nutritional choices and their impact on academic performance and perceived professional competence among college professors in select districts of Karnataka, India. A descriptive research design was employed, with data collected from 250 assistant and associate professors using stratified random sampling. A structured questionnaire captured insights on nutritional awareness, dietary habits, socio-economic influences, and academic performance. The findings revealed a significant positive correlation between nutritional awareness and academic performance, highlighting the role of balanced dietary habits in enhancing professional competence. Socio-economic factors were found to significantly influence food choices, underscoring regional disparities. Statistical analyses, including correlation, t-tests, and Chi-square tests, affirmed these relationships. The study concludes that fostering nutritional awareness and addressing socio-economic barriers are vital to improving health and professional outcomes in academic settings.